Tillage Effects on Spatiotemporal Variability of Particulate Organic Matter. (15th October 2009) - Lee, Juhwan; Laca, Emilio A.; van Kessel, Chris; Rolston, Dennis E.; Hopmans, Jan W.; Six, Johan
Abstract : This study was performed to evaluate effects of no-till (NT) and standard tillage (ST) on POM in two 15-ha neighboring fields from 2003 to 2004. We also evaluated the effects of minimum tillage (MT) on POM after both NT and ST fields were converted to MT in the summer of 2005. We quantified C and N stocks of three size fractions (53–250, 250–1000, and 1000–2000 μ m ) of POM (0–0.15 m depth). The POM-C 53–250 μ m and 250–1000 μ m fractions decreased by 25% and 36% after six months under ST, whereas relatively little change occurred under NT, suggesting significant tillage effects over the period 2003-2004. Only small changes in POM content then occurred under MT on both fields. Changes in POM-N were similar to POM-C changes upon tillage conversions. This suggests that reduced tillage did not lead to soil C increase compared to ST but may help maintain the level of soil C for a typical California farming system. Short-term, field level variability of POM was primarily affected by tillage and was further influenced by clay content, bulk density, and scale of observation.